Adequacy and effectiveness of Uganda’s gambling regulatory framework - Ahaibwe, Gemma; Lakuma, Corti Paul; Katunze, Miriam; Mawejje, Joseph (Economic Policy Research Centre, 2016)
In light of the likely negative impacts of gambling, the industry needs to be strictly controlled, well regulated and effectively policed. Presently, the gambling industry is regulated by the National Lotteries Board (NLB) and is guided by the National Lotteries Act of 1967, the Gaming and Pool Betting (Control and Taxation) Act of 1968, and an addendum of statutory guidelines introduced in 2012/13. Findings from the desk review and key informant interviews reveal that many facets of the laws relating to lottery and gaming have become obsolete and are not sensitive to the new modes of gambling and the unprecedented growth of the industry. Furthermore, the National Lotteries Board (NLB) has substantial capacity problems and limited statutory powers and is not always able to effectively exercise its mandate herein inhibiting its ability to comprehensively regulate the gambling industry.